Anti-Müllerian hormone is correlated with cumulative live birth in minimal ovarian stimulation with clomiphene citrate: a retrospective cohort study - Kenji Ezoe; Xiaowen Ni; Tamotsu Kobayashi; Keiichi Kato (BMC, 2020)
Abstract Background Several studies have investigated the correlation between the serum anti-Müllerian hormone (AMH) level and in vitro fertilization (IVF) outcomes in controlled ovarian stimulation cycles; however, studies regarding the correlation of the serum AMH level with IVF outcomes in minimal ovarian stimulation cycles remain limited. In this study, we aimed to analyze the correlation of the serum AMH level with ovarian responsiveness, embryonic outcomes, and cumulative live birth rates in clomiphene citrate (CC)-based minimal ovarian stimulation cycles. Methods Clinical records of 689 women whose entire ovarian stimulation regimen consisted solely of minimal stimulation cycle IVF using CC alone from November 2017 to October 2019 were retrospectively reviewed. The association between IVF outcomes and the serum AMH level before the initiation of the first fertility treatment was analyzed. Furthermore, the correlation of the serum AMH level with cumulative live birth rates after IVF treatment was assessed. The Cochran-Armitage test, Pearson's chi-squared test, Spearman rank correlation test, Student's t-test, one-way analysis of variance, logistic regression analysis, Kaplan-Meier method and Cox proportional hazards model were used to analyze the data. Results The serum AMH level positively correlated with the number of retrieved oocytes, blastocyst formation rate, blastocyst cryopreservation rate, and live birth rate per oocyte retrieval in CC-based minimal ovarian stimulation cycles without any exogenous gonadotropin administration. Furthermore, the cumulative live birth rate and treatment period required for conceiving were strongly associated with the serum AMH level at the initiation of fertility treatment. Conclusions A low serum AMH level correlated with low ovarian responsiveness, impaired pre-implantation embryonic development, and decreased cumulative live birth rate in CC-based minimal ovarian stimulation cycles. Therefore, the cycle success rate would be predicted by measuring the serum AMH level in minimal ovarian stimulation with CC alone.